Variabel-variabel yang Mempengaruhi Inflasi di Indonesia - Dea Anggraeni; Inayati Nuraini Dwiputri (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2022)
Inflation is one of the economy's most important indicators and an economic challenge that is a concern for developing countries such as Indonesia. This study aims to analyze the influence of several variables that are suspected of having an influence on inflation in Indonesia. The independent variables include the money supply, BI rate, exchange rate, Gross Domestic Product, and imports. Data were obtained from the Bank Indonesia and Badan Pusat Statistik (BPS) from 2010 to 2020. This study uses the Error Correction Model (ECM) to determine the effect of the independent variables in the short and long term. The study concluded that the money supply had a positive but not significant effect in the short term, but in the long term had a significant effect on inflation. The BI and exchange rates have a significant and positive effect on long-term and short-term inflation. Gross Domestic Product does not have a significant positive effect on inflation in both the long and short term. Imports show a positive but not significant with inflation in the long and short term.